PENGARUH KOMPETENSI PETANI TERHADAP KELESTARIAN HASIL DAN USAHA HUTAN RAKYAT JATI DI KABUPATEN MUNA, SULAWESI TENGGARA - Musdi Musdi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Farm forestry is one form of farming business developed by the community in Muna District. Farm forestry businesses are expected to provide product for supporting farmer economic condition. Sustainable farm forestry management must be supported by competent farmers. Farmer’s competencies consisting of knowledge, skills, attitudes, and actions have not been identified, therefore it is necessary to conduct an assessment to determine their performance in order to maintain and improve the yield and business of farm forestry. This study aims to analyze the relationship between farmer competence and the sustainability of farm forestry product and business. Data collection was taken by using purposive sampling. Data analysis uses Structural Equation Modeling (SEM) which is operated by the Linear Structural Relationship (LISREL) program. Farm forestry business is not a main livelihood for the community which makes the farmers’ income does not depend on their farm forestry earnings. The results of this study indicate that the competency of farm forestry farmers and its several influencing factors have a significant impact on farm forestry sustainable management, especially in terms of product and business sustainability.